STRUCTURAL MODELING OF INNOVATION CLUSTER INNOVATION CLUSTER’S INSTITUTIONAL ENVIRONMENT - D. L. Napolskikh (Модернизация, инновация, развитие)
The modern state of the problem of modeling the internal and external environment of the innovation cluster is considered. The proposed organizational model of interaction between the institutions of the cluster and the environment, as well as model and institutional infrastructure component of the cluster are offered. A hypothesis on the need for the organic model of the institutional environment of innovation cluster is offered.